PARADIGMA PENDIDIKAN TRADISIONAL SEBAGAI MODAL PENDIDIKAN TRANSFORMASIONAL - Syafrawi Syafrawi (Universitas Islam Madura, 2018)
Education is a process of the changeperson attitude or behaviorto mature human being through the effort of teaching implementation by sticking to the norm that has long been happened from young generation to next generation. Traditional education is synonymous with pesantren which the implementation is carried out in an informal way through takhassus approach, and regeneration. Islamic perspective of science comes from God. If there are differences between sense and revelation,Islamic thinkers will be more trustworthy and mandatory of the truthrevelationauthority than the result of sensing, because the truth of revelation is regarded as true and absolute truth. InIslamicClassical, education is devided into two categories: formal and informal institutions (kuttab, shuffauh, halaqoh, qushur, majlis and mosque and clerical house) and they have their own characteristics. The orientation of traditional education is to carry the sacred duty of spreading religion. Preserving the teachings of Islam, the Reaching of the Eucharist, Focused on Islamic Educational Science, teacher-centered Education, Traditional education system of learning, they still use halaqoh system, gather, group up afterwards forward one by one. This model of education is then used as capital to transform education; it means that the education quality is better than before.